2017
DOI: 10.1155/2017/5309081
|View full text |Cite
|
Sign up to set email alerts
|

Periductal Mastitis: An Inflammatory Disease Related to Bacterial Infection and Consequent Immune Responses?

Abstract: Periductal mastitis (PDM) is a prolonged inflammatory disease, but the cause of PDM is poorly understood. In the present case control study, 87 PDM and 87 healthy controls were enrolled and the results were evaluated to identify the significant risk factors for PDM. To investigate the roles of bacterial infection and critical cytokines expression, 16S rRNA gene sequencing and bacterial culturing were conducted. We also measured the levels of interferon-γ, interleukin-12A, and interleukin-17A by semiquantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
16
1
2
Order By: Relevance
“…Some studies implicate age as one of the risk factors for the development of many benign breast disorders, the age was not a risk factor in our study, and the correlation was not significant when compared to the controls (P value 0.324). Obesity also have been implicated by some authors to have a possible association, although in this study this correlation was not present (P value 0.831) [ 6 , 12 ].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Some studies implicate age as one of the risk factors for the development of many benign breast disorders, the age was not a risk factor in our study, and the correlation was not significant when compared to the controls (P value 0.324). Obesity also have been implicated by some authors to have a possible association, although in this study this correlation was not present (P value 0.831) [ 6 , 12 ].…”
Section: Discussioncontrasting
confidence: 61%
“…The tissue examination showed various degrees of inflammation, infiltration with chronic inflammatory cells particularly plasma cells, and foam cell formation, breast duct dilatation, periductal fibrosis, intraepithelial histiocytes, calcifications in duct lumen or duct wall, and abscess formation [ 3 , 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the risk of breast cancer in women increased significantly as the occurrence of non-lactational mastitis increased. Non-lactational mastitis is known to be related to chronic inflammation secondary to infection-induced cytokines 30 , as well as inflammatory, infectious, hormonal and autoimmunity factors 31,32 . Reportedly, the presence of exogenous and endogenous pathogen-associated molecular patterns (PAMPs) (bacteria, viruses and fungi, as well as endogenous molecules released from injured or dying cells) can cause the activation of inflammatory pathways 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, IGM usually involves a tender mass and is typically peripheral and unilateral. Other common clinical findings include a nonbloody nipple discharge and nipple retraction (61), which are uncommon with IGM. Mammary duct ectasia may be more confidently diagnosed when similar imaging features are seen bilaterally.…”
Section: Mammary Duct Ectasiamentioning
confidence: 99%